2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6943085
|View full text |Cite
|
Sign up to set email alerts
|

Sampling-based tree search with discrete abstractions for motion planning with dynamics and temporal logic

Abstract: This paper presents an efficient approach for planning collision-free, dynamically-feasible, and low-cost motion trajectories that satisfy task specifications given as formulas in a temporal logic, namely Syntactically Co-Safe Linear Temporal Logic (LTL). The planner is geared toward high-dimensional mobile robots with nonlinear dynamics operating in complex environments. The planner incorporates physics-based engines for accurate simulations of rigid-body dynamics.To obtain computational efficiency and genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…DROMOS is compared with LTLSYCLOP and to a more recent LTL motion planner . Scalability is evaluated by increasing the number of goals and color groups.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DROMOS is compared with LTLSYCLOP and to a more recent LTL motion planner . Scalability is evaluated by increasing the number of goals and color groups.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Comparison results DROMOS is compared with LTLSYCLOP and to a more recent LTL motion planner , referred to as LTLIROS 14, which was shown to be faster than LTLSYCLOP . These motion planners converted the LTL formula into an automaton using techniques from model checking, and then combined the LTL automaton with the adjacency graph of a workspace triangulation in order to guide the motion‐tree expansion.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works [21,22,23,24] propose incorporating both the robot dynamics and the given LTL constraints in a continuous space. A continuous state space can be abstracted into a discrete state space and a continuous path is derived by sampling guided by the high-level discrete plan [22,23,24]. Other works have focused on grounding natural language to LTL expressions [9,10,17] to further allow a robot to make use of these LTL specifications.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover a lazy-search approach was used for the high level planning thus resulting in computational speedups by 10 times for the second order non-linear hybrid controller compared with the previous method. Moreover sampling based Tree-Search motion planning with discrete abstractions for specifications using temporal logic proposed by McMahon et al [8]. In this framework the authors suggested very low cost motion trajectories that satisfy CoSafe LTL.…”
Section: Related Workmentioning
confidence: 99%